Jejak Historis Tantrayana di Pura Dalem Dasar Purwa Desa Pengastulan Kabupaten Buleleng - Kurnia Dewi, Ni Made Evi (Jurnal Penelitian Agama Hindu, 2025)
The statue of Goddess Durga and the childbirth statue are examples of sexual sculptures in Pura Dalem Dasar Purwa, Pengastulan Village, which reflect the teachings of Tantrayana. Their existence is believed to symbolize safety and fertility, influencing religious ritual activities. This research aims to examine the influence of Tantrayana on the sexual statues at Pura Dalem Dasar Purwa and its impact on the Hindu community in Pengstulan Village. This study employs a qualitative method with a theological approach. Data collection methods include observation, interviews, and literature study. The results of this study show that the statue of Goddess Durga is one form of yantra application in worshiping Sakti, believed to be a symbol of protection and serves as the foundation for the implementation of the mapinunasan gegemet (protection) ritual to Ida Bhatari Dalem. This practice is a significant feature of tantric belief, an esoteric practice of power and Sakti's expression. Another statue reflecting the influence of tantra is the childbirth statue or brayut statue, believed to symbolize fertility. This statue serves as the basis for the ritual activity of mapinunasan sentana (descendants) by the local Hindu community. The presence of these sexual statues has impacted the social and religious life of Hindus in Pengstulan Village, especially for those who have succeeded and benefited from the practice of mapinunasan. It has strengthened solidarity bonds, manifested through communal activities. The conclusion of this study is that the statue of Goddess Durga and the childbirth statue reflect the teachings of Tantrayana, believed to be symbols of safety and fertility. Their existence influences religious rituals in Pura Dalem Dasar Purwa, which in turn affects the social and religious life of the Hindu community in Pengstulan Village.